Penentuan Produk Unggulan Daerah pada Sentra Industri Kecil Menengah di Kabupaten Bondowoso - Moh Erfan Arif (Universitas Tarumanagara, 2021)
This study aims to determine the Regional Superior Products (PUD) in Bondowoso Regency, East Java Province. Bondowoso Regency has several industrial centers that produce regional potential products that can become superior products. The potential industrial centers include coffee, tape, brass, furniture, baskets, iron crafts, embroidery, chips, tiles, batik, and bricks. The determination of this regional superior product refers to Permendagri Number 9 of 2019 concerning Regional Superior Product Development. This research method is descriptive qualitative with the method of collecting data through interviews. The results showed that the potential industrial centers that were eligible to be designated as regional superior products were the tape industry centers. The industrial centers that produce these tapes are the most appropriate to be designated as Bondowoso Regency's Superior Products because they are the most suitable and reflect the criteria of regional superior products according to Permendagri number 9 of 2019. The results of the determination of the superior products of this region can be used as a basis in the preparation of potential industrial center development programs to increase regional economic growth. Penelitian ini bertujuan untuk menentukan Produk Unggulan Daerah (PUD) di Kabupaten Bondowoso Provinsi Jawa Timur. Kabupaten Bondowoso memiliki beberapa sentra industri yang menghasilkan produk-produk potensial daerah yang dapat menjadi produk unggulan. Sentra-sentra industri potensial tersebut antara lain: kopi, tape, kuningan, mebel, besek, kerajinan besi, bordir, keripik, genteng, batik, dan batu bata. Penentuan produk unggulan daerah ini mengacu Permendagri Nomor 9 Tahun 2019 tentang Pengembangan Produk Unggulan Daerah. Metode penelitian ini adalah deskriptif kualitatif dengan metode pengumpulan data melalui wawancara. Hasil penelitian menunjukkan bahwa sentra industri potensial yang layak ditetapkan sebagai produk unggulan daerah adalah sentra industri tape. Sentra industri yang menghasilkan tape ini paling layak ditetapkan sebagai Produk Unggulan Daerah Kabupaten Bondowoso karena paling sesuai dan mencerminkan kriteria-kriteria produk unggulan daerah sesuai Permendagri Nomor 9 Tahun 2019. Hasil penentuan produk unggulan daerah ini dapat dijadikan dasar dalam penyusunan program pengembangan sentra industri potensial untuk meningkatkan pertumbuhan ekonomi daerah.